CURRICULUM, ISLAMIC UNDERSTANDING AND RADICAL ISLAMIC MOVEMENTS IN INDONESIA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2016)
This article is intended to argue several things. The first is that the educational institutions can play two roles within the context of transmitting Islamic understanding; either to preach the tolerance or in contrast the radicalism. The second is that the teachers affiliated to certain radical movements often fall in to corrupt practices by abusing the school curriculum, which actually is aimed at providing guideline for the teachers of Islamic Religion in order to promote characters of students in line with the values of Indonesia Islam. The third is that the condition and the environment of schools tend to allow the room for the deployment process of radical movements in Indonesia. This article will explore issues on the relationship between school curriculum and radicalism, the transmission of Islamic understanding as well as possible solutions for overcoming the spread of radicalism. In conclusion, this article will reinforce ideas that teachers are the most important instruments within the curriculum implementation. In this regards, it is important to note that curriculum in its various forms is just a text and hence the teachers are the ones really determine the ways in which it is being read and interpreted. It is suggested then that there is a duty that should be performed by the government to strengthen their ideology based on the country national guidelines embraced by Muslims in Indonesia.